2020
DOI: 10.1519/jsc.0000000000003492
|View full text |Cite
|
Sign up to set email alerts
|

Early Season Hormonal and Biochemical Changes in Division I Field Hockey Players: Is Fitness Protective?

Abstract: Walker, AJ, McFadden, BA, Sanders, DJ, Bozzini, BN, Conway, SP, and Arent, SM. Early season hormonal and biochemical changes in Division I field hockey players: is fitness protective? J Strength Cond Res 34(4): 975–981, 2020—The purpose was to evaluate changes in hormonal and biochemical markers as a result of the accumulated stress of the initial 4-week training block in field hockey players. Women's Division I field hockey players (N = 22; Mage = 19.7 ± 1.1 years) performed testing before the start of presea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…In fact, and as it happened with END response, plasma ACTH and PRL concentrations reached their maximum values at t3 (increases of 287% and 150%, respectively, in relation to baseline conditions). Moreover, our results are in consonance with those previously reported by Pompe et al (2001), who found similar responses of ACTH and PRL after high-intensity exercises, but contrary to those described by Choi et al (2013) and Bosco et al (1996) (van Paridon et al, 2017;Walker et al, 2019Walker et al, , 2020, the psychophysiological role of these hormones during exercise does not seem to be sufficiently defined. Thus, further investigation focused on PRL responses to exercise-induced stress is important since PRL could also be involved in reproductive cycle dysfunction and contribute to the female athlete triad (Walker et al, 2019(Walker et al, , 2020.…”
Section: © Editorial Committee Of Journal Of Human Kineticssupporting
confidence: 84%
See 3 more Smart Citations
“…In fact, and as it happened with END response, plasma ACTH and PRL concentrations reached their maximum values at t3 (increases of 287% and 150%, respectively, in relation to baseline conditions). Moreover, our results are in consonance with those previously reported by Pompe et al (2001), who found similar responses of ACTH and PRL after high-intensity exercises, but contrary to those described by Choi et al (2013) and Bosco et al (1996) (van Paridon et al, 2017;Walker et al, 2019Walker et al, , 2020, the psychophysiological role of these hormones during exercise does not seem to be sufficiently defined. Thus, further investigation focused on PRL responses to exercise-induced stress is important since PRL could also be involved in reproductive cycle dysfunction and contribute to the female athlete triad (Walker et al, 2019(Walker et al, , 2020.…”
Section: © Editorial Committee Of Journal Of Human Kineticssupporting
confidence: 84%
“…Moreover, our results are in consonance with those previously reported by Pompe et al (2001), who found similar responses of ACTH and PRL after high-intensity exercises, but contrary to those described by Choi et al (2013) and Bosco et al (1996) (van Paridon et al, 2017;Walker et al, 2019Walker et al, , 2020, the psychophysiological role of these hormones during exercise does not seem to be sufficiently defined. Thus, further investigation focused on PRL responses to exercise-induced stress is important since PRL could also be involved in reproductive cycle dysfunction and contribute to the female athlete triad (Walker et al, 2019(Walker et al, , 2020. Despite this, SAn decreased at this timepoint assessment compared to t2, whilst being slightly higher than the values registered at t0.…”
Section: © Editorial Committee Of Journal Of Human Kineticssupporting
confidence: 84%
See 2 more Smart Citations
“…Detected changes in phosphorus-calcium metabolism, leukocytosis with segmented shift, increase of alkaline phosphatase, uric acid and serum iron, changes of the liver echogenicity, pancreas and gallbladder are probably associated with an alimentary factor [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%